2007
DOI: 10.1093/jxb/erm154
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent endogenous oxygen concentration regulates microsomal oleate desaturase in developing sunflower seeds

Abstract: Oleoyl-phosphatidylcholine desaturase (FAD2) is a key enzyme involved in fatty acid desaturation in oilseeds, which is affected by environmental temperature. The results of this study show that FAD2 is regulated in vivo via temperature-dependent endogenous oxygen concentrations in developing sunflower (Helianthus annuus L.) seeds. By combining in vivo oxygen profiling, in situ hybridization of FAD2 genes, an assay of energy status, fatty acid analysis, and an in vitro FAD2 enzyme activity assay, it is shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 49 publications
3
58
0
1
Order By: Relevance
“…There have been some previous reports about the relationship between the fatty acid composition and environmental conditions. For example, Rolletschek et al (2007) reported about fatty acid composition in developing sunflower seeds, the effect of environmental temperature and the key enzyme involved in fatty acid desaturation. The key enzyme was oleoylphosphatidyl choline desaturase which is responsible for the desaturation of oleic acid into linoleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some previous reports about the relationship between the fatty acid composition and environmental conditions. For example, Rolletschek et al (2007) reported about fatty acid composition in developing sunflower seeds, the effect of environmental temperature and the key enzyme involved in fatty acid desaturation. The key enzyme was oleoylphosphatidyl choline desaturase which is responsible for the desaturation of oleic acid into linoleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Oil content and composition are modified by high constant temperature during sunflower grain development, and previous reports indicated a marked reduction in the percentage of linoleic acid in standard sunflower oil, apparently due to the effect of temperature on the activity of the enzyme oleate desaturase, which is responsible for the conversion of oleic to linoleic acid (Flagella et al 2002, Grompone 2005. Garcés and Mancha (1991), who established that the oleyl-phosphatidylcholine-desaturase activity, in sunflower, is inhibited at temperatures above 20 °C, specifically investigated this effect and Rolletschek et al (2007), afterwards, demonstrated the mechanism by which temperature modifies the unsaturation degree of the sunflower oil through its effect on dissolved oxygen levels in the developing seed.…”
Section: A Regitano Neto Et Almentioning
confidence: 99%
“…The biosynthetic pathways leading to the formation of oil fatty acids have been widely studied in oilseeds, such as sunflower (Helianthus annuus L.) (Garcia-Diaz et al, 2002;Rondanini et al, 2003;Rolletschek et al, 2007;Zlatanov et al, 2009), groundnut (Arachis hypogaea L.) (Hassan et al, 2005b), rapeseed species (Brassica sp.) (Bhardwaj and Hamama, 2003), safflower (Carthamus tinctorius L.) (Rahamatalla et al, 2001) and cuphea (Cuphea sp.)…”
mentioning
confidence: 99%